2018
DOI: 10.1371/journal.pone.0194138
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characterization of influenza virus infections in children with severe acute respiratory infection in Maputo, Mozambique: Results from the implementation of sentinel surveillance, 2014 – 2016

Abstract: In Sub-Saharan Africa, where burden, impact, and incidence of acute respiratory infections (ARI) are the highest in the world, conversely, the epidemiology of influenza-associated severe acute respiratory infections (SARI) is incompletely known. The aim of this study was to describe the clinical and epidemiological features of influenza-associated SARI in hospitalized children in Maputo city, Mozambique. Nasopharyngeal and oropharyngeal swabs were collected from children aged 0–14 years old who met the case de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…the burden of SARI focus on viral infections in children [8][9][10][11]. A SARI surveillance study in China revealed that 90% of patients were aged <15 years [12].…”
Section: Plos Onementioning
confidence: 99%
“…the burden of SARI focus on viral infections in children [8][9][10][11]. A SARI surveillance study in China revealed that 90% of patients were aged <15 years [12].…”
Section: Plos Onementioning
confidence: 99%
“…it is possible to raise the hypothesis of an underdiagnosis of pediatric cases in Maputo. Although, in recent years, there has been an improvement in the tracking and diagnosis of these cases, resulting from the qualification and training of clinicians in the field of pediatric TB (Ministry of Health of Mozambique, 2014; Nguenha et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the southern region of Mozambique, where Maputo is located, almost 70,000 people migrate annually to work in the mines of South Africa, a country that holds 3% of the TB load in the world (Southern Africa Tuberculosis and Health Systems [SATBHSS], 2017;WHO, 18;Mathema et al 2015). In Mozambique, in the district of Manhiça, TB notifications from 1997 to 2012 are three times higher than in other areas, being higher for men than for women (Nguenha et al 2018). Despite data being available at the regional level, the temporal trend of TB in the capital Maputo has been little explored to support intervention measures aimed at TB prevention and control.…”
Section: Introductionmentioning
confidence: 99%
“…While, the acute infection of the pulmonary parenchyma, developing outside the hospital or diagnosing within 48 hours of admission to the hospital, was credited as community‐acquired pneumonia (CAP), which was common in children . According to the epidemiological investigation, CAP was believed as one of the most severe acute respiratory infections (ARI), approximately accounting for 80% of all deaths suffering from this disease, which was more frequent in developing countries . Moreover, the incidence rate of CAP in children was nearly 22%, and there were about 55,000 children deaths every year caused by CAP in China .…”
Section: Introductionmentioning
confidence: 99%
“…respiratory infections (ARI), approximately accounting for 80% of all deaths suffering from this disease, 5 which was more frequent in developing countries. 6 Moreover, the incidence rate of CAP in children was nearly 22%, and there were about 55,000 children deaths every year caused by CAP in China. 7 Although the pathological mechanism of CAP has not been clearly elucidated, many researchers have focused their attentions on genetic factors in CAP.…”
mentioning
confidence: 99%